Analysis of the effectiveness of Corporate Social Responsibility in brand marketing with AAKER Brand Equity and Daisy Wheel Models - Amoako, Kwasi; Boateng, Elvis (Technium Social Sciences Journal, 2022)
Corporate Social Responsibility (CSR) have a great capacity to influence society to create that good brand equity. In light of this, many organizations now have ardent reputation in promoting CSR activities in the interest of society. Through review of related studies and survey questionnaires to both staff and customers of Accra Breweries Ltd (ABL), this paper sought to broadly analyze the effectiveness of Corporate Social Responsibility on Brand Marketing with emphasis on the use of Aaker Brand Equity and Daisy Wheel Models. Specifically, the study aimed at identifying the factors that influence involvement in CSR activities by corporations; and the influence CSR grants have on the public perception and brand marketing. The study employed primary data and secondary data sources. Purposive sampling technique was used to select 20 senior/middle staff and 40 customers of ABL. The findings revealed that, CSR programmes are community-focus initiatives, involves programmes on education as well as health programmes in developing communities. The study therefore concluded that, CSR activities go a long way to build a solid brand identity and equity as in the case of ABL. It is therefore recommended that CSR initiative should engage all stakeholders who are mostly affected to help tailor CSR activities to solve societal needs.